Effect of carbohydrate mouth rinse on performance after prolonged submaximal cycling - Jensen, M. M.; Klimstra, M.; Sporer, B.; Stellingwerff, T. (Medicine & Science in Sports & Exercise, 2018)
Previous studies have shown improved shorter duration (~1 h) performance with carbohydrate (CHO) mouth rinsing (WASH), especially in overnight fasted/non-fuelled subjects.